The endothelial plasma membrane lipidome and its remodeling under hyperglycemia: an exploratory study - Reis, Ana; Sohrabi, Yahya; Diaz-Sanchez, Lorena; Dias Araújo, Ana Rita; Leffers, Merle; Antonny, Bruno; Rudnitskaya, Alisa; Vitorino, Rui; Dias, Irundika H. K. (Frontiers in Molecular Biosciences, 2026)
IntroductionAt the interface between blood and blood vessels, the endothelial plasma membrane is the first point of contact to external stimuli, triggering the cascade of intracellular events responsible for proper vascular function. However, the endothelial plasma membrane lipidome and its remodeling in pathological conditions remain largely unknown.MethodsTo address this gap, we present a comprehensive lipidomic analysis of cell-derived giant plasma membrane vesicles isolated from primary human umbilical vein endothelial cells cultured in vitro under normoglycemic conditions and their lipid remodeling in adaptation to hyperglycemia.ResultsUsing targeted mass spectrometry-based strategies, 251 lipids and 13 oxidized lipids from 20 subclasses were identified and quantified. Cholesterol accounted for almost half (45 mol%) of the membrane’s composition. In adaptation to hyperglycemia, the noticeable decrease in the total phospholipids extracted resulted in an increased cholesterol-to-phospholipid (Chol/PL) ratio, which is consistent with increased membrane stiffening. Several other lipid subclasses, namely, lysolipids, phosphatidylcholines, aminophospholipids, polyunsaturated sphingomyelins, and other polyunsaturated phospholipids, showed a decreasing trend. Oxysterols displayed a shift toward the predominance of enzymatic (tail-oxidized) in hyperglycemia, whereas truncated oxidized phosphatidylcholines (oxPC) with a terminal aldehyde moiety exhibited a decreasing trend, suggesting the formation of lipid–protein cross-linking modification.DiscussionThe hyperglycemia-induced alterations provide insights into the endothelial membrane lipid environment and the biophysical dynamics that are likely to deregulate protein–lipid interactions involved in sugar and lipid metabolism. The high amount of Chol found in our work serves as the basis for future in silico simulations crucial for drug design and drug response evaluation.